2015
DOI: 10.21071/az.v64i245.375
|View full text |Cite
|
Sign up to set email alerts
|

ALIMET® (análogo líquido de metionina hidroxilada) en el sistema inmunitario, población de microflora y rendimiento de broilers

Abstract: Este experimento se realizó para investigar el efecto de niveles crecientes de ALIMET ® (hidroxi análogo líquido de la metionina) en la dieta de broilers sobre los anticuerpos séricos, población microbiana y crecimiento. Se utilizó un diseño completamente al azar. Trescientos pollos Ross 308, no sexados fueron aleatoriamente asignados a 4 tratamientos con tres repeticiones de 25 pollos cada una. Los tratamientos incluían un control y tres niveles de suplementación de ALIMET ® (1,150, 1,437 y 1,725 g/kg en las … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…We noted that at high-dose level, HMTBA supplementation had higher ADG and ADFI than for DLM (Vazquez-Anon et al, 2006). Therefore, HMTBA is suggested to outperform DLM when TSAA values are above requirement (Agostini et al, 2016;Vazquez-Anon et al, 2006) Previous research found that HMTBA supplementation decreased the pH of the feed but had no significant effect on pH of duodenum, jejunum, ileum, and cecum contents (Krutthai et al, 2015;Salary, Kalantar, Dashtbin, & Matin, 2015). However, in the current study, higher HMTBA supplementation did not reduce dietary pH.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…We noted that at high-dose level, HMTBA supplementation had higher ADG and ADFI than for DLM (Vazquez-Anon et al, 2006). Therefore, HMTBA is suggested to outperform DLM when TSAA values are above requirement (Agostini et al, 2016;Vazquez-Anon et al, 2006) Previous research found that HMTBA supplementation decreased the pH of the feed but had no significant effect on pH of duodenum, jejunum, ileum, and cecum contents (Krutthai et al, 2015;Salary, Kalantar, Dashtbin, & Matin, 2015). However, in the current study, higher HMTBA supplementation did not reduce dietary pH.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous research found that HMTBA supplementation decreased the pH of the feed but had no significant effect on pH of duodenum, jejunum, ileum, and cecum contents (Krutthai et al., 2015; Salary, Kalantar, Dashtbin, & Matin, 2015). However, in the current study, higher HMTBA supplementation did not reduce dietary pH.…”
Section: Discussionmentioning
confidence: 96%